2015
DOI: 10.1177/0265407515573601
|View full text |Cite
|
Sign up to set email alerts
|

Is friendship quality reflected in memory narratives?

Abstract: The purpose of this study was to explore the link between friendship quality and content and structure of autobiographical narratives about friends. Gender differences were investigated as well. A total of 93 Italian undergraduates (51 males and 42 females) were asked to recall memories about their friends. Then, they were requested to write in detail one of their recalled memories. The Network of Relationships Inventory was used to measure the participants’ friendship dimensions. The results showed that males… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 56 publications
1
12
0
Order By: Relevance
“…Thus, the difference in number of words between groups was not a factor. In terms of the linguistic characteristics of the narratives, as we hypothesized and has been found by others [8,55], women's narratives were longer than men's. However, in Tani et al, only narratives about friends were investigated.…”
Section: Discussionsupporting
confidence: 73%
See 4 more Smart Citations
“…Thus, the difference in number of words between groups was not a factor. In terms of the linguistic characteristics of the narratives, as we hypothesized and has been found by others [8,55], women's narratives were longer than men's. However, in Tani et al, only narratives about friends were investigated.…”
Section: Discussionsupporting
confidence: 73%
“…These researchers, along with Williams-Baucom, Atkins, Sevier, Eldridge, and Christesen [37], concluded that proportionately greater use of 'We' and lesser use of 'I' seem to be linguistic indicators of higher quality and stability of a couple's relationship. Differential use of 'I' and 'We' has also been found to be associated with quality of friendship relationships [8]. When young women were asked to write a detailed narrative about a memory that involved their best friend, those with more qualitatively positive friendship relationships used proportionately fewer first person singular ('I') and more first person plural ('We') pronouns.…”
Section: Narratives -The Language Of Memoriesmentioning
confidence: 99%
See 3 more Smart Citations